2019
DOI: 10.1210/en.2018-00924
|View full text |Cite
|
Sign up to set email alerts
|

Chronic High-Fat Diet Exacerbates Sexually Dimorphic Pomctm1/tm1 Mouse Obesity

Abstract: Mice with a targeted mutation in the pro-opiomelanocortin ( Pomc ) gene ( Pomc tm1/tm1 mice) are unable to synthesize desacetyl- α -MSH and α -MSH and they develop obesity when fed chow diet. In this study, we hypothesized that a chronic high-fat (HF) diet exacerbates Pomc tm1/tm1 mouse obesity. Male and female Pomc wt/wt and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 44 publications
4
46
0
Order By: Relevance
“…Male C2CD5KO mice significantly consumed more food during light phase with no significant differences seen during dark phase (Figure 2M). Before BW diversion, female C2CD5KO mice consumed significantly more calories than WT mice (8 weeks of age) only when fed WD (Supplementary 1H) consistent with the BW data (showing no difference between WT and KO when fed NC) and with the hypothesis that hypothalamic C2CD5 may be involved in the exacerbation of sexually dimorphic obesity induced by chronic western-diet [39]. Thus, lack of C2CD5 causes hyperphagia in males when fed NC or WD and in females when fed WD.…”
Section: Resultssupporting
confidence: 74%
“…Male C2CD5KO mice significantly consumed more food during light phase with no significant differences seen during dark phase (Figure 2M). Before BW diversion, female C2CD5KO mice consumed significantly more calories than WT mice (8 weeks of age) only when fed WD (Supplementary 1H) consistent with the BW data (showing no difference between WT and KO when fed NC) and with the hypothesis that hypothalamic C2CD5 may be involved in the exacerbation of sexually dimorphic obesity induced by chronic western-diet [39]. Thus, lack of C2CD5 causes hyperphagia in males when fed NC or WD and in females when fed WD.…”
Section: Resultssupporting
confidence: 74%
“…Before BW diversion, female C2CD5KO mice consumed significantly more calories than WT mice (8 weeks of age) only when fed WD (Supplementary 1H) consistent with the BW data (showing no difference between WT and KO if NC-fed). This finding also supports the hypothesis that hypothalamic C2CD5 may be involved in the exacerbation of sexually dimorphic obesity induced by chronic western-diet [39]. Thus, lack of C2CD5 causes hyperphagia in NC-and WD-fed male, and in WD-fed female mice.…”
Section: Hyperphagia and Energy Expenditure In C2cd5ko Micesupporting
confidence: 87%
“…Recent data shows the evidence of a sexual dimorphic nature of the brain in its response to high fat diet and in many cases, the use of chronic high fat diet exacerbates sexually dimorphic mouse obesity. Hubbard et al showed that hypothalamic MC4R ligands are required for observing sexual dimorphism [39]. More investigations will be necessary to evaluate whether gonadal hormones regulate hypothalamic C2CD5 and define such a sexual dimorphic mouse obesity.…”
Section: Mice Lacking C2cd5 Develop Obesitymentioning
confidence: 99%
“…Our findings also suggest sexual dimorphism in the melanocortin system, as the lack of Efnb2 in POMC neurons does not lead to impaired gluconeogenesis in females, but it does result in changes to refeeding after an overnight fast. The ARH has not been primarily viewed as a dimorphic structure, but recent studies showed differences between males and females in the number of ARH POMC neurons, their firing rate, the development of diet-induced obesity and the activation of STAT3 in POMC neurons (4446).…”
Section: Discussionmentioning
confidence: 99%